The Effect of Adding Core Stability Training to Plyometric Training on Increasing Jump Height in Basketball Athletes - Ahmad Falahudin; Alen Rismayadi; Geraldi Novian (Universitas Negeri Semarang, 2025)
The purpose of this study was to investigate the effect of adding core stability training to plyometric training on increasing the jump height of basketball athletes. The method used in this study was an experimental method with a Pretest-Posttest Control Group Design research design. The study population consisted of 20 Kamimasae KU Club basketball athletes aged 16-18 years, who were also the research sample, selected using a total sampling technique. The instrument used in this study was the Vertical Jump Test. Data analysis was conducted using the Paired Sample T-Test statistical test with the aid of the SPSS version 30 application. The results showed that there was a significant effect of adding core stability training to plyometric training on increasing the jump height of basketball athletes. The experimental group that received plyometric training with additional core stability experienced an average increase of 6%, while the control group that was only given plyometric training experienced an average increase of 3%. The conclusion is that adding core stability training to plyometric training is significantly more effective in increasing vertical jump height than plyometric training alone.